Prevention and treatment for iron-deficiency anemia in obstetrical gynecological practice - М.S. Selikhova; P.A. Soltys; L.S. Kalacheva (LCC «Medicine-Inform», 2020)
М.S. Selikhova, P.A. Soltys, L.S. Kalacheva Volgograd State Medical University, Volgograd, Russian Federation The prevalence of iron-deficiency anemia (IDA) is steadily increasing. IDA is more common in women of reproductive age, pregnant women, and adolescent girls thus accounting for the importance of this issue in obstetrics and gynecology. Abnormal uterine bleeding (AUB) is one of the most common causes of IDA both in the puberty and reproductive period which requires hemostasis as well as addressing iron deficiency. A high rate of IDA was also reported in women with pelvic inflammatory diseases; this should considered when managing this large group of gynecological patients. The treatment for anemia or latent iron deficiency is performed for a long time, therefore, the selection of a medication is particularly important. Peroral Tardyferon® containing 80 mg of iron meets all modern-day requirements for anti-anemic drugs and is recommended for anemia resulting from AUB both in women of reproductive age and adolescent girls. Case studies illustrate high efficacy and good tolerability of this medication. Keywords: iron-deficiency anemia, pregnancy, abnormal uterine bleeding in puberty, heavy menstrual bleeding, genital inflammation, high efficacy, compliance. For citation: Selikhova М.S., Soltys P.A., Kalacheva L.S. Prevention and treatment for iron-deficiency anemia in obstetrical gynecological practice. Russian Journal of Woman and Child Health. 2020;3(4):276-281. DOI: 10.32364/2618-8430-2020-3-4-276-281.